Journalistic Views on Hard and Soft News: Cross-Validating a Popular Concept in a Factorial Survey. (September 2019) - Glogger, Isabella; Otto, Lukas P.
Despite the popularity of the concept of hard and soft news, researchers regularly criticize the vague definitions and inconsistent conceptualizations. Following claims for standardization of concept in journalism research, this article aims to cross-validate the most recent understanding of the concept. We conducted a factorial survey with newspaper journalists to probe the question as to which of the theoretically assumed dimensions of the concept are referred to by journalists to distinguish hard from soft news. We find the dimensions "topic, " "relevance, " "framing, " and "opinion" to exert influence on journalists' understanding of the concept.